2018
DOI: 10.31234/osf.io/8vwf6
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Burden of Online Friends: The Effects of Giving Up Facebook on Stress and Well-Being

Abstract: People occasionally choose to cut themselves off from their online social network by taking extended breaks from Facebook. This study investigated whether abstaining from Facebook reduces stress but also reduces subjective well-being because of the resulting social disconnection. Participants (138 active Facebook users) were assigned to either a condition in which they were instructed to give up Facebook for five days or continue to use Facebook as normal. Perceived stress and well-being, as well as salivary c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 21 publications
3
21
0
Order By: Relevance
“…Effects on perceived stress were not statistically significant, but the mean scores between the two groups were in the expected direction at postintervention. Previous studies have similarly found that a period of abstinence from social media use results in a decline in stress and a concurrent decline in well‐being . The present study's findings echo this pattern of results, which at first glance appear at odds with each other.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Effects on perceived stress were not statistically significant, but the mean scores between the two groups were in the expected direction at postintervention. Previous studies have similarly found that a period of abstinence from social media use results in a decline in stress and a concurrent decline in well‐being . The present study's findings echo this pattern of results, which at first glance appear at odds with each other.…”
Section: Discussionsupporting
confidence: 83%
“…Previous studies have similarly found that a period of abstinence from social media use results in a decline in stress and a concurrent decline in well-being. 8,34,56 The present study's findings echo this pattern of results, which at first glance appear at odds with each other. The following hypothesis is offered as an attempt to explain this finding.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations